FAKTOR-FAKTOR YANG MEMPENGARUHI PRAKTEK PERATAAN LABA PADA PERUSAHAAN MANUFAKTUR DI BEI - LUSI CHRISTIANA (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
Income smoothing is a way which done by the management company to reach certain profit targets for companies needed and private needed. Income smoothing action would be detrimental to the users of financial statements, whether principal or investors and creditors. Therefore, the writer wanted to know whether the firm size, profitability, financial leverage and dividend payout ratio will affect the management to take action income smoothing. The writer uses the population of companies that listed on the Indonesia Stock Exchange, while the sample using a manufacturing company from 2008, 2009, and 2010. The writer uses the method of purposive sampling and selecting the 60 companies in the sample study. The writer uses secondary data from financial statements of listed manufacturing companies in Indonesia Stock Exchange. The writer uses binary logistic regression methods to examine the influence of company size, profitability, financial leverage and dividend payout ratio, to income smoothing action. Eckel index results showed that 23 manufacturing companies are not included income smoothing into income smoothing and 37 manufacturing companies that are included in the income smoothing group. Based on the results of binary logistic regression analysis, firm size, profitability, financial leverage and dividend payout ratio has no effect on income smoothing action.